2018
DOI: 10.1590/rbz4720160234
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and histologic responses of pacu (Piaractus mesopotamicus) fed diets supplemented with increasing concentrations of ractopamine

Abstract: An experiment was conducted during 60 days with forty pacu males fed diets supplemented with increasing concentrations of ractopamine (0.00, 11.25, 22.50, 33.75, and 45.00 mg kg −1). Eight fish were evaluated for each experimental diet. Performance and survival rate of the fish were measured. At the end of the experiment, blood was collected to determine the levels of cortisol, triacylglycerol, and protein. Moreover, the liver was collected to determine the activities of glucose-6phosphate dehydrogenase and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…7 Aquaculture Nutrition Dietary ractopamine supplementation was found to be beneficial in lowering body lipid and raising body protein in all-female prawns in our study, as it has been previously reported for blue catfish I. furcatus [30] and channel catfish I. punctatus [13] fed with the beta-adrenergic agonist compounds L644, 969, and ractopamine, respectively. Drumond et al [33] reported the reduction of lipid deposition between muscle fibers in pacu. Similarly, the addition of 8 mg/kg ractopamine to the feed altered the abdominal muscle chemical composition of Nile tilapia, where the treated fish had a 23.3% lower lipid content than the control fish [5].…”
Section: Discussionmentioning
confidence: 99%
“…7 Aquaculture Nutrition Dietary ractopamine supplementation was found to be beneficial in lowering body lipid and raising body protein in all-female prawns in our study, as it has been previously reported for blue catfish I. furcatus [30] and channel catfish I. punctatus [13] fed with the beta-adrenergic agonist compounds L644, 969, and ractopamine, respectively. Drumond et al [33] reported the reduction of lipid deposition between muscle fibers in pacu. Similarly, the addition of 8 mg/kg ractopamine to the feed altered the abdominal muscle chemical composition of Nile tilapia, where the treated fish had a 23.3% lower lipid content than the control fish [5].…”
Section: Discussionmentioning
confidence: 99%
“…A higher dose of ractopamine of 45 mg kg −1 increased the protein, and lower dose of 11.25 mg kg −1 ractopamine reduced the ether extract level in the fillets. The lipid deposition between muscle fibres of Pacu was also found to be reduced (Drumond et al, 2018). The supplementation of ractopamine and l-carnitine results in muscle protein accretion, nitrogen retention by increased synthesis and reduction in the degradation of protein but accelerates fatty acid oxidation (Ji et al, 1996;Salem et al, 2006).…”
Section: Discussionmentioning
confidence: 99%